Object-oriented JavaScript - Stefanov, Stoyan; Sharma, Kumar Chetan (Packt Publishing, 2013)
Annotation Think in JavaScript Make object-oriented programming accessible and understandable to web developers Apply design patterns to solve JavaScript coding problems Learn coding patterns that unleash the unique power of the language Write better and more maintainable JavaScript code Type in and play around with examples that can be used in your own scripts.
Keywords: Computer software -- Reusability.; JavaScript (Computer program language); Object-oriented programming (Computer science); Software patterns.; elektronické knihy; electronic books